Immunohistochemical localization of metallothionein in developing rat tissues. - Hisao Nishimura; Noriko Nishimura; Chiharu Tohyama (1989)
Metallothionein (MT) is a cysteine-rich, low molecular weight protein inducible by heavy metal ions and various endogenous factors. Using an indirect immunofluorescent technique, we studied the localization of MT in developing rat tissues (kidney, small intestine, and liver). In kidney of the neonate and fetus, MT was found in both the cytoplasm and the nucleus of renal tubular epithelia. Localization of MT changed with shift of zonation in the renal cortex during development. Metallothionein was found mainly in the inner zone of the cortex but not in tubules of the neogenic zone on Day 4. Until Day 18, tubular cells containing MT were observed in a part of the cortex adjacent to the medulla, followed by a significant decrease in immunostaining by Day 27. In small intestine of the neonate, MT was localized predominantly in Paneth and goblet cells which play secretory roles. The number of goblet cells with strong immunostaining for MT was maximal on Day 27. In liver of 20-day fetuses and of 4-day-old neonates, both the cytoplasm and the nucleus of hepatocytes exhibited strong immunofluorescence. The intensity of MT staining diminished with development, and by 18-27 days after birth no immunofluorescence was observed in the nucleus. We further studied a possible association of MT with development by localizing MT in livers obtained from partially hepatectomized and laparotomized rats. Hepatectomy led to the appearance of MT not only in the nucleus and cytoplasm of hepatocytes but also in sinusoids and bile canaliculi. After laparotomy, MT immunofluorescence was observed only in the cytoplasm. The present results suggest a possible involvement of MT in cell proliferation and differentiation, as well as in transport and secretion of this metal-binding protein.